Skepticism - Machuca, Diego E.,Reed, Baron (Bloomsbury Academic, 2018)
Skepticism: From Antiquity to the Present' is an authoritative and up-to-date survey of the entire history of skepticism. Divided chronologically into ancient, medieval, renaissance, modern and contemporary periods and featuring 50 specially-commissioned chapters from leading philosophers, this comprehensive volume is the first of its kind. By exploring each of the distinct traditions and providing expert insights, this extensive reference work: - covers major thinkers such as Cicero, Descartes, Hume, Spinoza and Wittgenstein - acknowledges the influence of ancient skeptical traditions on later philosophy and explains why it is still a fertile topic of inquiry among today's philosophers and historians of philosophy - analyses various forms of skepticism including Pyrrhonian, religious, ethical and Neo-Pyrrhonian - addresses issues in contemporary epistemology and indicates new directions of study Skepticism, a driving force in the history of philosophy, remains at the centre of debates in ethics, philosophy of religion, epistemology and the philosophy of mind
Keywords: Skepticism